THE INFLUENCE OF SERVICE QUALITY AND PRICE PERCEPTION ON REUSE INTEREST IN GRAB MOTOR CONSUMERS IN JOMBANG - SA'ADAH , LAILATUS; MU'AROFAH , MEILIYA (International Journal of Social and Management Studies, 2021)
The purpose on the study he purpose of this study was to determine and analyze the effect of service quality and price perception on the re-use interest of Grab Motor consumers in Jombang. By using accidental sampling technique a number of 97 respondents. The results in this study on multiple linear regression analysis can be seen that the R square value is 0.481, which means that advertising and brand image can explain the consumer buying interest factor of 48.1% and the remaining 51.9% is explained by other factors. And in the f test, it can be seen that the probability value is 0.000 < 0.05. Thus, it can be seen that the variables of service quality and price perception simultaneously (simultaneously) have a significant effect on repurchase interest. The results of the T test show that the significance value of t = 0.000 is smaller than the value of = 0.05, which means that service quality has a significant influence on (reuse interest. The t-count value of price perception shows the significance value of t = 0.013 which is smaller than the value of = 0 .05. This means that price perception has a significant effect on interest in reuse. The better the quality of service, the higher the interest in reuse and Price is very important in determining the interest in reuse of a product/service. The better the perception of price, the higher the interest in reuse.